Grove Mountains 020090 enriched lherzolitic shergottite: A two‐stage formation model. (13th September 2013) - Lin, Yangting; Hu, Sen; Miao, Bingkui; Xu, Lin; Liu, Yu; Xie, Liewen; Feng, Lu; Yang, Jing
Abstract: Grove Mountains (GRV) 020090 is an enriched lherzolitic shergottite, distinct from other lherzolitic shergottites, except RBT 04262/1. Its characteristics include high abundance of plagioclase (24.2 vol% in the nonpoikilitic area), presence of K‐feldspar, common occurrence of baddeleyite, high FeO contents of olivine (bimodal peaks at Fa 33 mol% and Fa 41 mol%) and low‐Ca pyroxenes (bimodal peaks at Fs 23.8–31.7 mol% and Fs 25.7–33.9 mol%), and significant LREE enrichment of phosphates (500–610 × CI). The bulk composition of GRV 020090 suggests derivation from partial melting of an enriched reservoir. However, the REE patterns of the cores of pigeonite oikocrysts and the olivine chadacrysts are indistinguishable from those of GRV 99027 and other moderately depleted lherzolitic shergottites, and reveal a LREE‐depleted pattern of the primordial parent magma. We propose that the primordial parent magma of GRV 020090 was derived from a moderately depleted Martian upper mantle reservoir, and later the residual melt was contaminated by oxidized and enriched Martian crustal materials as it ascended up to the subsurface. GRV 020090 and RBT 04262/1 may have sampled an igneous unit different from other lherzolitic shergottites.